IMPLEMENTASI SISTEM INFORMASI AKUNTANSI TERHADAP PROSES BISNIS UMKM MAKANAN TRADISIONAL TIGA PUTRA TASIKMALAYA - Lina Marlina; Sriyanti Nurfadilah; Baiq R Ulinuha (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2023)
The use of digitalization that has not been optimal will create challenges in time speed, procedural errors, it is feared that it will reduce business processes due to decreased customer satisfaction. Business processes require technological assistance for traditional food MSME players in Tasikmalaya to improve operational efficiency. More in-depth research is needed on the factors that make business processes effective in MSMEs. The purpose of this study was to analyze the results of the implementation of accounting information systems on business processes based on previously implemented systems in traditional Tasikmalaya food MSMEs in supporting business sustainability in the digital era. The research method uses a qualitative descriptive method approach using interviews with research subjects, namely the management of traditional Tasikmalaya food as informants. Data sources use primary data, and data collection techniques by interview. The results showed that the implementation of accounting information systems greatly helped the business processes of traditional food MSMEs. accounting information systems contribute to business processes including customer satisfaction levels, operational efficiency, process cycle time, error rates. Suggestions for business management to adopt technology with accounting information systems to improve business processes. Future research can explore other technologies that make it easier for MSME management to develop their business. Keywords: Computerized System; Business process; MSMEs